2023
DOI: 10.1002/anie.202311373
|View full text |Cite
|
Sign up to set email alerts
|

Is “Water in Salt” Electrolytes the Ultimate Solution? Achieving High Stability of Organic Anodes in Diluted Electrolyte Solutions Via a Wise Anions Selection

Amey Nimkar,
Khorsed Alam,
Gil Bergman
et al.

Abstract: The introduction of the water‐in‐salt (WIS) concept, using highly concentrated electrolyte solutions to prevent water splitting and widen the electrochemical stability window, has greatly influenced modern aqueous batteries. The successful implementation of these electrolyte solutions in many electrochemical systems shifts the focus from diluted to WIS electrolyte solutions. Considering the high costs and the tendency of these nearly saturated solutions to crystallize, this trend can be carefully re‐evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The rate performance of carbonyl electrodes can be influenced by salt concentration, additives, and interfacial chemistry. For example, the PTCDA electrode exhibits capacities of approximately 90, 53, and 17 mAh g –1 at 10 A g –1 in 1, 0.5, and 0.2 M NaClO 4 aqueous electrolytes, respectively (Figure a) . The enhanced rate performance of PTCDA in electrolytes with higher concentrations is attributed to the higher availability of the Na + ions near the electrode surface and the higher conductivity.…”
Section: Electrolyte and Interfacial Chemistry Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate performance of carbonyl electrodes can be influenced by salt concentration, additives, and interfacial chemistry. For example, the PTCDA electrode exhibits capacities of approximately 90, 53, and 17 mAh g –1 at 10 A g –1 in 1, 0.5, and 0.2 M NaClO 4 aqueous electrolytes, respectively (Figure a) . The enhanced rate performance of PTCDA in electrolytes with higher concentrations is attributed to the higher availability of the Na + ions near the electrode surface and the higher conductivity.…”
Section: Electrolyte and Interfacial Chemistry Regulationmentioning
confidence: 99%
“…For example, the PTCDA electrode exhibits capacities of approximately 90, 53, and 17 mAh g −1 at 10 A g −1 in 1, 0.5, and 0.2 M NaClO 4 aqueous electrolytes, respectively (Figure 5a). 63 The enhanced rate performance of PTCDA in electrolytes with higher concentrations is attributed to the higher availability of the Na + ions near the electrode surface and the higher conductivity. Of course, considering that the viscosity of the electrolyte increases with the concentration, the higher the concentration of the electrolyte is not the better for the rate performance of electrodes.…”
Section: Rate Performancementioning
confidence: 99%
See 1 more Smart Citation
“…, the stability of sodium ion embedded in the cathode is not determined by its concentration but by the properties of its anti-ion. 90 Through electrochemical analysis and theoretical calculation, they proved that the anode performance is mainly dominated by the anionic solvation characteristics. Therefore, it is possible to achieve aqueous sodium-ion batteries with excellent performance at low temperatures by selecting the appropriate anions.…”
Section: Low Fusion-point Co-solventsmentioning
confidence: 99%
“…Electrolytes play an important role in the dissolution of organic electrode materials and the solvation/desolvation of charge carriers. Electrolyte engineering has been considered an effective strategy to improve the electrochemical performance of organic materials for PIBs. For example, both Lu’s and Song’s groups demonstrated that the electrochemical performance of perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) can be significantly elevated by using a high-concentration electrolyte. Bai et al achieved a superior cycling stability (only a capacity decay of 20 mAh g –1 after 320 cycles) of 3,4,9,10-perylenetetracarboxylic diimide in an ether-based electrolyte .…”
mentioning
confidence: 99%